GRANULOMA PIOGENIK MULTIPEL - Lawalata, Tracy O.H.; Tjahjadi, Aris A.; Oroh, Elly E. Ch.; Suling, Pieter L. (JURNAL BIOMEDIK : JBM, 2010)
ABSTRACT: Pyogenic granuloma is a benign proliferating vascular tumor of the skin and mucous membrane that follows a minor injury or infection. This tumor occurs mostly in children or young adults and can be detected as a bright red solitary papule or nodule with a diameter of 5-10 mm that grows rapidly within 1-3 weeks. The papule or nodule is often covered by a subtle collaret of scales, brittle, and easily bleeding even with minor trauma. Methods of treatment are excision, electro surgery, cryosurgery, laser, or combinations thereof, and imiquimod cream. We reported a case of a 27-year-old male who had suffered from six reddish papules on the back of his left ear for six months. It began with one milliar tumor in size then there arose five other tumors around it, rapidly growing, which easily bled within several weeks. Skin lesions were multiple pedunculated erythematous papules, tender, and 0.2-0.5 cm in diameter. Histopathological features demonstrated a pyogenic granuloma. The treatment which performed a shave excision followed by electro surgery had a satisfactory outcome. Keywords: multiple pyogenic granuloma, shave excision.  ABSTRAK : Granuloma piogenik merupakan tumor vaskuler proliferatif jinak pada kulit dan membran mukosa yang sering mengikuti suatu trauma minor atau infeksi. Tumor ini lebih sering terjadi pada anak dan dewasa muda. Lesi berupa papul atau nodul soliter berwarna merah terang dengan ukuran 5-10 mm, tumbuh cepat dalam 1-3 minggu namun rapuh, seringkali dengan koleret skuama halus dan mudah berdarah dengan trauma ringan. Terapi dapat berupa bedah eksisi, bedah listrik, bedah beku, laser atau kombinasi diantaranya, dan krim imiquimod. Kami melaporkan satu kasus granuloma piogenik multipel dan penatalaksanaannya pada seorang laki-laki berusia 27 tahun dengan enam benjolan berwarna merah pada bagian belakang telinga kiri sejak enam bulan yang lalu. Awalnya hanya berupa satu benjolan sebesar kepala jarum pentul, kemudian setelah beberapa minggu timbul lima benjolan lain disekitarnya yang cepat membesar, serta mudah berdarah. Kelainan kulit berupa papula eritem, multipel, bertangkai, teraba kenyal,  dan berdiameter 0,2?0,5 cm. Gambaran histopatologik menunjukkan suatu granuloma piogenik. Penatalaksanaan yang dilakukan dengan shave excision diikuti bedah listrik memberikan hasil yang memuaskan. Kata kunci: granuloma piogenik multipel, shave excision.